Evaluation of initial dofetilide dosing recommendation based on actual body weight in overweight and obese patients. (14th September 2015) - Cao, D. X.; Kohatsu, A.; Eng, L.; Mei, K.; Dinh, J.; Mok, I.; Moreau, N.; Le, A.; Shin, J.
Summary: What is known and objective: The dofetilide label recommends using actual body weight (ABW) to calculate the Cockcroft–Gault creatinine clearance (CrCl) for the determination of the initial dose; however, few studies have attempted to evaluate this dosing recommendation in overweight and obese patients. We evaluated whether the current dofetilide dosing recommendation based on ABW is appropriate in overweight and obese patients. Methods: This is a retrospective cohort study conducted at two large academic medical centres in the United States on overweight and obese patients (body mass index ≥ 25 kg/m 2 ) who were newly started on dofetilide based on ABW. Patients were categorized into (i) the different‐dose group if their CrCl calculated based on the ideal body weight (IBW) resulted in a lower initial dofetilide dose compared with ABW‐based CrCl and (ii) the same‐dose group if they would have the same initial dose based on IBW and ABW. The primary outcome was dofetilide dose reduction or discontinuation due to prolongation of the corrected QT interval during the first 3 days of dofetilide therapy. Multivariable logistic regression analysis was performed to identify factors predicting the risk of primary outcome. Results and discussion: Of the 132 patients included in the study, 29 (22·0%) were in the different‐dose group and 40 (30·3%) had the primary outcome. The per cent of patients with the primary outcome was not statistically significantly different between the different‐dose and same‐dose groups (37·9% vs. 28·2%; P = 0·31). Diabetes mellitus was a significant predictor for the primary outcome (odds ratio 2·54; 95% confidence interval 1·05–6·15). What is new and conclusion: Our study provides the evidence on the safety of the current dofetilide dosing recommendation in overweight and obese populations in clinical practice. Current ABW‐based dofetilide dosing is reasonable in overweight and obese patients. Abstract : This study evaluated whether the current dofetilide dosing recommendation based on actual body weight (ABW) is appropriate in overweight and obese patients. In this study, patients were categorized into 1) the different‐dose group if their creatinine clearance (CrCl) calculated based on the ideal body weight (IBW) resulted in a lower initial dofetilide dose compared to ABW‐based CrCl; and 2) the same‐dose group if they would have the same initial dose based on IBW and ABW. The study found that dofetilide dose reduction or discontinuation due to prolongation of the corrected QT interval during the first 3 days of dofetilide therapy was not statistically different between the two categories of patients, providing the evidence that current ABW‐based dofetilide dosing is reasonable in overweight and obese patients.